Difference Spectrophotometric Method for the Determination of Metronidazole in Tablets - H.S. Ahmida, Nagwa; A. Esmael, Mona; A. Winse, Eman; El-Enany, N.; Belal, F. (Asian Journal of Chemistry, 2010)
In this work, a simple, sensitive and rapid spectrophotometric method is proposed for determination of metronidazole. The method is based on the induced spectral changes upon changing the pH of the medium and measured the difference in absorbance at 326 nm. The difference absorbance (ΔA) is linear in the concentration over the range 2.0-40.0 μg/mL (r2 = 0.999), with a detection limit 0.76 μg/mL. The method was successfully applied to the commercial pharmaceutical drug without interference from common ingredients accompanying the drug. The obtained results are in good agreement with those obtained by official methods.